Broadway bound - Simon, Neil (Random House, 1987)
Neil Simon continues the semiautobiographical trilogy begun with Brighton Beach Memoirs and Biloxi Blues. Broadway Bound begins with the efforts of Eugene Jerome and his older brother to launch a career as a comedy writing team.